2004
DOI: 10.1007/bf02659712
|View full text |Cite
|
Sign up to set email alerts
|

Industry-specific human capital and the wage profile: Evidence from Taiwan

Abstract: Using data from Taiwan's Manpower Utilization Survey (1979Survey ( -1999, this paper finds evidence that supports the industry-specific human capital effect on wage tenure profiles. We examine data on people who voluntarily or involuntarily change job within or across industries last year. Pre-switching work experience is used as an indirect measure for testing the industry-specific human capital by comparing the effect between stayers and movers. Other things being equal, holding firm tenure constant movers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Neal (1995) concluded that wages significantly reflected compensation for industry-specific human capital, among those with experience. Furthermore Chuang and Lee (2004) identified that industry-specific human capital was the strongest contributor to an individual’s wage profile, out of all the types of human capital. The publications of Carmichael (1983), Neal (1995), Lazear (2009) and Raffiee and Coff (2016) reflected firm-specific and industry-specific human capital as: the seniority and the length of service of the employee (Carmichael, 1983) and organisational routines and culture (Raffiee and Coff, 2016) (firm-specific human capital); and attending seminars, reading/writing publics and interactions with colleagues and fellow academics (Lazear, 2009) (industry-specific human capital).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Neal (1995) concluded that wages significantly reflected compensation for industry-specific human capital, among those with experience. Furthermore Chuang and Lee (2004) identified that industry-specific human capital was the strongest contributor to an individual’s wage profile, out of all the types of human capital. The publications of Carmichael (1983), Neal (1995), Lazear (2009) and Raffiee and Coff (2016) reflected firm-specific and industry-specific human capital as: the seniority and the length of service of the employee (Carmichael, 1983) and organisational routines and culture (Raffiee and Coff, 2016) (firm-specific human capital); and attending seminars, reading/writing publics and interactions with colleagues and fellow academics (Lazear, 2009) (industry-specific human capital).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This implied that an individual with more human capital would draw a greater income than another with less human capital. However, a more focussed theory by Neal (1995) stated that wages/income, in part, reflect the amount of industry-specific skills and knowledge an individual has acquired, and which, according to Chuang and Lee (2004) is the form of human capital that mattered most in determining an individual’s wages. The latter theory focussed on industry-specific human capital.…”
Section: Hypothesis Developmentmentioning
confidence: 99%